2020
DOI: 10.1002/anie.202010794
|View full text |Cite
|
Sign up to set email alerts
|

Carbide Dihydrides: Carbonaceous Species Identified in Ta4+‐Mediated Methane Dehydrogenation

Abstract: The products of methane dehydrogenation by gas‐phase Ta4+ clusters are structurally characterized using infrared multiple photon dissociation (IRMPD) spectroscopy in conjunction with quantum chemical calculations. The obtained spectra of [4Ta,C,2H]+ reveal a dominance of vibrational bands of a H2Ta4C+ carbide dihydride structure over those indicative for a HTa4CH+ carbyne hydride one, as is unambiguously verified by studies employing various methane isotopologues. Because methane dehydrogenation by metal catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Similarly, it seems unlikely that the second dehydrogenation is too fast for the H/D-exchange reaction to compete with, when one considers that for products of Ta + and Ta 2 + this exchange is clearly visible in spite of much faster dehydrogenation reactions. Instead, this peculiar behavior may rather be related to the particular structure of [Ta 4 (CH 2 )] + , which was identified by us with IR spectroscopy of exhibiting a carbide dihydride structure, that is, H 2 Ta 4 C + …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, it seems unlikely that the second dehydrogenation is too fast for the H/D-exchange reaction to compete with, when one considers that for products of Ta + and Ta 2 + this exchange is clearly visible in spite of much faster dehydrogenation reactions. Instead, this peculiar behavior may rather be related to the particular structure of [Ta 4 (CH 2 )] + , which was identified by us with IR spectroscopy of exhibiting a carbide dihydride structure, that is, H 2 Ta 4 C + …”
Section: Resultsmentioning
confidence: 94%
“…“H/D exchange” indicates whether this reaction was directly observed or required in the simulations (“yes) or it could have been omitted (“no”). “moieties bound to tantalum” gives the functional groups for C and H species from our calculations (see section to follow) or the literature (in case of [TaCH 2 ] + , and [Ta 4 (CH 2 )] + and [Ta 4 (CH 2 ) 2 ] + ). When the species represent the final product of the different reaction with methane, it is denoted by “product”. b Rate coefficients referenced to [TaCH 2 ] + formation determined by Shayesteh et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While gas phase ions containing noble metals have good activity toward coupling of CH 4 molecules, researchers have also paid attention to ions containing non‐noble metals to find active species exhibiting comparable performance with noble metal systems. The reactions of positively charged bare tantalum clusters Ta n + ( n =1‐10) and oxygen deficient Ta n O m + ( m =1 and 2) clusters with CH 4 have been systematically investigated by a cryogenic ring electrode ion trap [12k,35,45,52] . It was found that the Ta 8 O 2 + cluster has the ability to catalyze the C−C coupling of two CH 4 to generate C 2 H 6 [35] .…”
Section: Coupling Reactions Of Ch4 Moleculesmentioning
confidence: 99%
“…The relative energies (in eV) of the corresponding structural isomers with respect to isomer II, the carbyne hydride. Adapted with permission from reference Lengyel et al (2020). Copyright (2020) Wiley‐VCH [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Intermediates In Methane Activationmentioning
confidence: 99%